The Effect of Intellectual Capital on Financial Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange - Mujiburrahman; Tarmizi (Indonesian Journal Economic Review (IJER), 2022)
This research was conducted with the aim of looking at the effect of intellectual capital on financial performance. This study uses a model developed by Pulic-Value Added Intellectual Coefficients (VAICTM). VAICTM is used to determine the efficiency of three intellectual capital models, namely capital employed, human capital and structural capital. In this context, Firer said the components used were VACA, VAHU and STVA as separate units. This study is to see the effect of VACA, VAHU and STVA on financial performance (ROA). The sample used in this study were 12 manufacturing companies listed on the Indonesia Stock Exchange during 2020 to 2022 and were taken by purposive sampling method. This research uses multiple linear regression analysis. The results of this study partially prove that VACA has a negative and significant effect on ROA, VAHU has a positive but not significant effect on ROA, STVA has a positive but not significant effect on ROA. This study also proves simultaneously that VACA, VAHU and STVA have a significant effect on ROA.